2019
DOI: 10.1038/s41419-019-2135-7
|View full text |Cite
|
Sign up to set email alerts
|

Snail modulates JNK-mediated cell death in Drosophila

Abstract: Cell death plays a pivotal role in animal development and tissue homeostasis. Dysregulation of this process is associated with a wide variety of human diseases, including developmental and immunological disorders, neurodegenerative diseases and tumors. While the fundamental role of JNK pathway in cell death has been extensively studied, its down-stream regulators and the underlying mechanisms remain largely elusive. From a Drosophila genetic screen, we identified Snail (Sna), a Zinc-finger transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…This was based on the RNA-Seq results, and we also validated these results using qPCR analysis (S3 Table and S7 Fig). Interestingly, the vertebrate Snail family proteins Snail1 and Snail2 regulate cell survival and apoptotic genes [89][90][91][92], and a recent study in Drosophila showed that snail specifically modulates the type of cell death mediated by c-Jun N-terminal Kinase [93]. Hence, Snail seems to partake in certain cell cycle events that are vital for normal growth of the endoreplicating tissue PG (endoreplication) as well as for cell death/survival.…”
Section: Snail As a Novel Regulator Of Endocycling In The Pgmentioning
confidence: 99%
“…This was based on the RNA-Seq results, and we also validated these results using qPCR analysis (S3 Table and S7 Fig). Interestingly, the vertebrate Snail family proteins Snail1 and Snail2 regulate cell survival and apoptotic genes [89][90][91][92], and a recent study in Drosophila showed that snail specifically modulates the type of cell death mediated by c-Jun N-terminal Kinase [93]. Hence, Snail seems to partake in certain cell cycle events that are vital for normal growth of the endoreplicating tissue PG (endoreplication) as well as for cell death/survival.…”
Section: Snail As a Novel Regulator Of Endocycling In The Pgmentioning
confidence: 99%
“…The c-Jun N-terminal kinase (JNK) is a member of the highly conserved MAPKs family that plays pivotal roles in various cellular processes including apoptosis [11][12][13][14][15]. basket (bsk) encodes the sole Drosophila JNK that is phosphorylated and activated by the conserved upstream MAPK cascade, including the JNKK kinase dTAK1 and the JNK kinase Hemipterous (Hep) [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…We counted the total number of migrating cells to quantify this phenotype and found that knockdown of Toll ‐ 7 resulted in decreased migrating cell number, while expression of Puc served as a positive control (Figure 1H–L, P). 44 Meanwhile, loss‐of‐ scrib also induced strong MMP1 expression, which is a biomarker for epithelial‐mesenchymal transition (EMT) 26,28,45 . Consistently, knockdown of Toll ‐ 7 suppressed scrib depletion‐induced MMP1 expression, while expression of Puc served as a positive control (Figure 1H’–L’, Q).…”
Section: Resultsmentioning
confidence: 71%